2019
DOI: 10.1016/j.ijheatmasstransfer.2018.12.107
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer and pressure drop characteristics of alternating clockwise and counter clockwise twisted tape inserts in the transitional flow regime

Abstract: The purpose of this study was to experimentally investigate the heat transfer and pressure drop characteristics in a smooth circular tube with alternating clockwise and counter clockwise twisted tape (CCCTT) inserts. The CCCTT inserts were fabricated from copper plate strips with a length, width and thickness of 450 mm, 18 mm and 1 mm respectively. The strips were twisted to obtain a twist ratio of 5 and 12 strips were joined longitudinally so that a clockwise direction twisted tape insert was connected to a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(36 citation statements)
references
References 77 publications
2
34
0
Order By: Relevance
“…Hence, all these changes can improve the heat performance in the grooved pipe compared to the normal one. These results agreed with References [2] and [6]. Figure 5 depicts the distributions in pressure inside both smooth and grooved pipes with different geometrical configurations.…”
Section: Validation Of Computational Calculation Proceduressupporting
confidence: 90%
See 1 more Smart Citation
“…Hence, all these changes can improve the heat performance in the grooved pipe compared to the normal one. These results agreed with References [2] and [6]. Figure 5 depicts the distributions in pressure inside both smooth and grooved pipes with different geometrical configurations.…”
Section: Validation Of Computational Calculation Proceduressupporting
confidence: 90%
“…To improve the convective heat transfer in the circular tubes, many types of turbulators have been applied. Turbulence is an important factor that has a direct effect on the thermal performance ratings, such as dimple, groove, 3,4 twisted tape, [5][6][7] wire coil, 8,9 and wing. 10 A numerical investigation of turbulent flows in the periodically grooved channels in 2D has been reported by Eiamsa-ard and Promvonge 11 with a range of Reynolds numbers 6000-18,000 and the (B/H) of 0.5-1.75, they found that the tube with groove increases the heat transfer up to 158% compared with the smooth tube, and the highest gain of 1.33 on thermal performance factor is obtained for the case of groove-width to the channel-height ratio by about 0.75.…”
Section: Introductionmentioning
confidence: 99%
“…At constant pumping power, the maximum thermal performance factor obtained is 1.433, 1.396 and 1.24 respectively for perforated twisted tapes with alternate axis, perforated twisted tapes and regular twisted tapes. Abolarin et al (2019) experimentally investigate the heat transfer and pressure drop characteristics in a smooth circular tube with alternating clockwise and counter clockwise twisted tape inserts. An increase in heat flux significantly enhanced the heat transfer in the laminar flow regime and delayed transition.…”
Section: Frontiers In Heat and Mass Transfermentioning
confidence: 99%
“…Bahiraei et al [14] have checked on a triple-tube that their outcomes show that, based on heat exchange efficiency, an increase in height and reduced pitch are suggested. Abolarin et al [15] have checked the impact of various geometries in twisted tapes, and the results pointed out that connection angle increases heat transfer. They found that when the wavelength is smaller, the temperatures near the walls increased.…”
Section: Introductionmentioning
confidence: 99%